RANCANG BANGUN SISTEM JARINGAN FAILOVER AUTOMATIC TELLER MACHINE (ATM) MELALUI JARINGAN PUBLIK BERBASIS PROTOCOL EOIP DAN P2TP - Ardiansyah, Rizka; Pratama, Septiano Anggun; Iskandar, Iskandar; Anshori, Yusuf; Komang, Gusti (Foristek, 2024)
The network on the Automatic Teller Machine currently uses a VSAT (Very Small Aperture Terminal) network based on Geostationary Satellites. VSAT networks often experience problems such as UP-DOWN or total DOWN. Some of the problems that cause interruptions on the VSAT interconnection include the usage period of the Modem electronic device and also ODU (Outdoor Unit) devices such as RFU, LNB, and BUC, ODU devices have a transmit period and also a received period that is uncertain according to the voltage at the location. Problems with the VSAT interconnection system cause ATM services to become unusable, resulting in losses for the bank's profits. In addition, the repair process is also generally quite time-consuming. The purpose of this study is to design an inexpensive ATM backup network solution so that when there is a break/disruption in the VSAT network the service on the ATM is not interrupted and in terms of operational costs does not swell. The backup network is intended to back up the satellite-based leading network automatically so that ATM services are always available when the satellite-based network is interrupted. The result of the study is that the proposed solution can resolve service outages at ATM machines in 34 seconds. The ATM network system will experience disconnection before finally reconnecting through the backup network. The proposed solution is much cheaper than the VSAT-based failover network solution, as it is based on the public internet network.